Effectiveness of various solvents in themicrowave-assisted extraction of cellulose from oil palm mesocarp fiber - Mohd Azlan, Nadiah Syafiqah; Yap, Chiew Lin; Gan, Suyin; Abdul Rahman, Mohd Basyaruddin (Elsevier, 2022)
Cellulose is a valuable resource for organic synthesis owing to its low cost, abundance, and sustainability. However, crystalline cellulose in lignocellulosic biomass is frequently smothered by the recalcitrant amorphous layers of lignin and hemicellulose that limit its extractability. Therefore, this study aimed to find the best solvent to combine with a microwave-assisted method for fast and efficient extraction of cellulose from oil palm mesocarp fiber. Results showed that γ-valerolactone gave the highest average cellulose yield (64.0%), followed by protic solvents viz. 2-butoxyethanol (62.8%) and ethyl lactate (57.3%), however, there was no statistical difference (p > 0.05) between the three solvents. Crystalline cellulose in biomass seems to interact with aprotic solvent via dipole–dipole interactions slightly more efficiently than with protic solvent via hydrogen bonds. However, as an aprotic solvent, ethyl acetate showed an exception low cellulose yield (50.7%), presumably due to its boiling point which is lower than the operating temperature. Among all, ILs ([BMIM][Cl], [HMIM][HSO4] and [EMIM][Ac]) performed the poorest giving only 36.0% to 52.0% of cellulose yields. The mixture of [HMIM][HSO4]/γ-valerolactone (1:1, v/v) performed similar to the sole [HMIM][HSO4]. Overall, the combination of γ-valerolactone and microwave extraction allowed a high yield of cellulose to be achieved within a short period of 2 min, at a relatively low temperature of 140 °C, although faint hydrolysis into glucose was detected. The cellulose extracted from γ-valerolactone showed a higher crystallinity index (46.81%) than raw biomass (24.06%), indicating a high purity product and the removal of amorphous portion.